2005
DOI: 10.1289/ehp.7570
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Pesticide Models of the Parkinson Disease Phenotype

Abstract: It has been hypothesized that developmental insults could contribute to Parkinson disease (PD), a neurodegenerative disorder resulting from the loss of the dopamine neurons of the nigrostriatal pathway. Two models of developmental pesticide exposures in mice are presented here that yield PD phenotypes consistent with this possibility. Combined exposures to the herbicide paraquat (PQ) and the fungicide maneb (MB), both of which adversely affect dopamine systems, administered from postnatal days 5–19, produced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(50 citation statements)
references
References 55 publications
2
47
0
1
Order By: Relevance
“…Thus, all of these data suggest that PD is a systemic degenerative disease that is not only affecting tissues in the BG, but also non cerebral tissues. This is consistent with the multiple-hit hypothesis (Cory-Slechta et al, 2005;Carvey et al, 2006) which predicts that multiple concurrent insults occurring at different target sites within a system (here nigrostriatal dopamine) may constrict the range and flexibility of compensatory mechanisms, thereby compromising the integrity and viability of the system.…”
Section: Introductionsupporting
confidence: 85%
“…Thus, all of these data suggest that PD is a systemic degenerative disease that is not only affecting tissues in the BG, but also non cerebral tissues. This is consistent with the multiple-hit hypothesis (Cory-Slechta et al, 2005;Carvey et al, 2006) which predicts that multiple concurrent insults occurring at different target sites within a system (here nigrostriatal dopamine) may constrict the range and flexibility of compensatory mechanisms, thereby compromising the integrity and viability of the system.…”
Section: Introductionsupporting
confidence: 85%
“…Various animal models have been developed to study the mechanistic and therapeutic intervention of PD, such as MPTP, paraquat, and maneb [15,16,20,22]. Combined exposure to paraquat and maneb is consistently used as pesticide-induced animal model of PD in mouse [7,15,16,20].…”
Section: Introductionmentioning
confidence: 99%
“…Cory-Schlecta suggested that when there are multiple risk factors, the system can no partial recovery of DA neurons. In PD progressive loss of DA neurons continues until the end of life; therefore longer "homeostatically reregulate itself," thus leading to damage (22,23). We have been testing the concept in this model does not reflect true progression.…”
mentioning
confidence: 99%